2
$\begingroup$

If $\alpha$ and $\beta$ are the roots of the quadratic equation $2x^2 + 4x -5 = 0$, evaluate $\alpha^3 + \beta^3$..

I know that $$\alpha + \beta = \frac{-b}{a}$$ and $$\alpha \beta = \frac{c}{a}\\$$ I also know that factorising $\alpha^3 + \beta^3 = (\alpha + \beta)(\alpha + \beta -\alpha \beta)$

I substituted everything in..

$$ (\frac{-4}{2})((\frac{-4}{2})-(\frac{-5}{2})) = -1 $$

Unfortunately, the answer in my text book says otherwise, it's supposed to be $-23$. What am I doing wrong? Thanks in advance!

$\endgroup$
  • 3
    $\begingroup$ Your factorisation is wrong, $\alpha^3+\beta^3 = (\alpha+\beta)(\alpha^2+\beta^2-\alpha\beta)$. But easier: $\alpha^3+\beta^3 = (\alpha+\beta)^3 - 3\alpha\beta(\alpha+\beta)$. $\endgroup$ – Daniel Fischer Oct 20 '14 at 12:21
  • $\begingroup$ Awkward.. Thank you! Well that was a stupid mistake.. Thanks again. $\endgroup$ – Samir Chahine Oct 20 '14 at 12:22
4
$\begingroup$

You have that $$\begin{align*}α^3+β^3&=(α+β)(α^2-αβ+β^2)=(α+β)(α^2+2αβ+β^2-3αβ)=\\&=(α+β)((α+β)^2-3αβ)\end{align*}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.